REDUCED BODY MASS INDEX BUT NOT FAT MASS IN ANTHRACYCLINE-BASED CHEMOTHERAPY OF LOCALLY ADVANCED BREAST CANCER PATIENTS - Isma Rachmawati; Raden Yohana; Bambang Amam; Yenni Zuhairini (IJCNP : INDONESIAN JOURNAL OF CLINICAL NUTRITION PHYSICIAN, 2023)
Background: Breast cancer is a cancer disease with the highest proportion of new cases and the proportion of deaths it causes is quite high at 6.9%. Cancer patients who use anthracycline-based chemotherapy experience loss of body weight, muscle, body cell mass, distribution of extracellular fluid expansion and reduced intracellular air. This study was to determine the change of the Body Mass index (BMI) and body composition of patients with locally advanced breast cancer (stage IIIA, IIIB and IIIC) who had undergone anthracycline-based chemotherapy.Methods: This anthracycline-based observational analytical study of pre and post chemotherapy was conducted with a cross-sectional approach. Subjects were measured height by microtoise; weight, body composition, daily calorie intake (DCI) and basal metabolic rate (BMR) as measured by Bioelectrical Impendance Analysis (BIA).Results: 47 locally advanced breast cancer patients underwent anthracycline-based chemotherapy. Based on the Wilcoxon statistical test, 6 variables with a 95% confidence level (p<0.05) showed a decrease in the value 5 variables, namely BMI, total body water (TBW), visceral fat, skeletal muscle mass and skeletal bone mass. Meanwhile, body fat showed a p value=0.224. The changes of variable confounding, DCI decrease (p=0.004), but BMR increase not significantly (p=0.795).Conclusion: There is an effect of chemotherapy on nutritional status of BMI, TBW, visceral fat, skeletal muscle mass and bone mass in patients with locally advanced breast cancer who underwent anthracycline-based chemotherapy, which may the result of the calorie intake decreased, but not on body fat